Nitrogen cycling and metabolism in the thalweg of a prairie river - Dodds, Walter K.; Beaulieu, J.J.; Eichmiller, J.J.; Fischer, J.R.; Franssen, N.R.; Gudder, D.A.; Makinster, A.S.; McCarthy, M.J.; Murdock, J.N.; O'Brien, J.M.; Tank, J.L.; Sheibley, R.W. (My University, 2012)
Nutrient dynamics in rivers are central to global biogeochemistry. We measured ammonium (NH4 +) uptake, metabolism, nitrification, and denitrification in the thalweg, the river region of greatest flow, of the Kansas River (discharge = 14,360 L/s). We estimated gross and net uptake with a depleted 15N-NH4 + release, metabolism with diel O2 measurements, and denitrification with dissolved N2 measurements. Net ecosystem production was negative. Net NH4 + uptake length was 2.1 km when concentrations were elevated, and gross uptake length was 1.9 km at ambient concentrations. Gross uptake rate measurements were comparable to estimates made using extrapolations from data obtained from streams (systems with 1/10th or less the discharge). Calculated lengths were maximal because the isotope pulse was primarily confined to the thalweg and not the shallow side channels or backwaters. Denitrification and nitrification rates were below detection. In the Kansas River, rates of N cycling are driven by heterotrophic processes, and considerable processing of N, particularly NH4 + uptake, occurred over a few kilometers of river length, with net uptake rates of NH4 + increasing with greater NH4 + concentrations.
Keywords: Nitrogen cycling; Nutrient dynamics in rivers; Thalweg; Kansas River; Metabolism